The dissolution of boundaries: landscape strategies applied to the Dipoli case - Cortés Sánchez, Luis Miguel; Cepeda, Javier Terrados; Savolainen, Panu (Landscape Architecture and Art, 2024)
The relationship between architecture and nature has always been one of the key topics of interest in architectural debate, even more so in the present day. Among the architectural approaches commonly described as “natural” and “landscape-oriented,” the work of Raili and Reima Pietilä stands out for the radical nature of its proposals in pursuit of an architecture that could be understood as inspired by natural forms in a specifically balanced manner, avoiding both the mere imitation of natural shapes, bordering on caricature, and illegible abstract interpretations. This article is based on the analysis of the design and construction of the Dipoli Centre (1961–66) as a paradigmatic example of this way of generating architecture inspired by the landscape or, in the words of the architects themselves, as an “extension of the landscape”. Through a detailed exploration of the graphic documents produced by the architects during the design and construction process of Dipoli, preserved in the archives of Arkkitehtuurimuseum, Museum of Finnish Architecture (MFA), as well as their conceptual descriptions and project reports, and an analysis of the built work itself, this article reveals the strategies and formal mechanisms through which the architects manage to present their architecture as a clear ‘continuation’ of nature, as a cultured extension of the Finnish landscape. These strategies can be encompassed within the concept of “dissolution of boundaries,” which manifests both in the architects’ metaphorical descriptions of the project and in the morphology of the building itself. The building is presented in such a way that no clear perimeter can be defined, but rather a diffuse, ambiguous territory of fragmented exchanges between exterior and interior. This idea is also reflected in the selection of construction components and basic materials —stone, concrete, wood, and copper— arranged in an innovative manner for its time, still unmatched today. In this approach, it becomes difficult to clearly define the boundary between the natural and the artificial, the preexisting and the superimposed, the interior and the exterior, and between the environment and the architectural artefact.